2021
DOI: 10.3390/ijms221910483
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Properties of Blackberry Anthocyanins in THP-1 Derived Macrophages

Abstract: An anthocyanin-rich diet is considered to protect against chronic inflammatory processes although the bioavailability of anthocyanins is regarded as rather low. Moreover, the immunomodulatory role of anthocyanins is not fully understood yet. In the present study, fractions of blackberry (Rubus fruticosus) juice were investigated in plasma-relevant concentrations with respect to their immunomodulatory properties in lipopolysaccharide (LPS)-challenged THP-1-derived macrophages. The complex blackberry extract act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…However, Del3-galactoside-which ranks third most abundant anthocyanin in our extractwas also reported as a main component [22,26]. In agreement with the literature, the BB extract only consists of cyanidin-based anthocyanins with Cy3glc (88.2% of total anthocyanins) as the major compound and small amounts of Cy3dioxglc, Cy3malglc, and Cy3xyl [23,27,28]. Cy3rut, representing 3% of total anthocyanins in the BB extract, was not detected in aforementioned publications, but Fan-Chiang et al reported a mean percentage of 10.2 Cy3rut in 51 blackberry samples from different American and international origins [29].…”
Section: Discussionsupporting
confidence: 91%
“…However, Del3-galactoside-which ranks third most abundant anthocyanin in our extractwas also reported as a main component [22,26]. In agreement with the literature, the BB extract only consists of cyanidin-based anthocyanins with Cy3glc (88.2% of total anthocyanins) as the major compound and small amounts of Cy3dioxglc, Cy3malglc, and Cy3xyl [23,27,28]. Cy3rut, representing 3% of total anthocyanins in the BB extract, was not detected in aforementioned publications, but Fan-Chiang et al reported a mean percentage of 10.2 Cy3rut in 51 blackberry samples from different American and international origins [29].…”
Section: Discussionsupporting
confidence: 91%
“…There is evidence indicating that higher education is associated with memory, executive function and language dysfunction in dementia patients and is related with faster cognitive decline on global cognition [41]. MUFA, Mg, Fe, Zn, vitamin E, thiamine, anthocyanins and isoflavones, which are recognized as anti-inflammatory parameters [42][43][44][45][46], were found to be much less consumed by MCI patients. Lymphocytes, as a key inflammatory response regulator, were down-regulated in MCI individuals.…”
Section: Discussionmentioning
confidence: 99%
“…It is a high-potassium and low-sodium fruit [4]. Blackberries also have unique healthcare functions [5]. For example, the total phenols in blackberries have antioxidant, heart protection, and lipid peroxidation-inhibiting effects [6].…”
Section: Introductionmentioning
confidence: 99%
“…Mounting evidence suggests that eating berries can provide antioxidant and anticancer protection for humans and animals [7]. It is an important source of people's intake of natural pigments, flavonoids, dietary fiber, vitamins, mineral elements and antioxidant substances [3,5,8]. With the development of the economy and the improvement of people's living standards, the blackberry market has broad prospects.…”
Section: Introductionmentioning
confidence: 99%